DAMPAK SERTIFIKASI DAN MOTIVASI KERJA GURU TERHADAP KINERJA GURU DI MTs NEGERI MODEL KURIPAN LOMBOK BARAT - Mimbar, Lalu; Izrawati, Izrawati; Kartini, Endang (Sekolah Tinggi Ilmu Ekonomi AMM Mataram, 2018)
This study aims to: 1) analyze the effect of teacher certification and work motivation on teacher's performance in MTs.Negeri Model Kuripan West Lombok, 2) to analyze teacher certification and work motivation have significant effect simultaneously on teacher's performance in MTs.Negeri Model of Kuripan West Lombok. Variables used are teacher certification, teacher work motivation, and teacher performance. The population of 40 civil servant and non-civil servant teachers, the samples selected are teachers who have certified both civil servants and non-civil servants as many as 35 people. The result of the research shows that Certification and Work Motivation have positive and significant influence simultaneously on Teacher Performance in MTs Model Model Kuripan, this is proved by the result of regression calculation seen from the value of F count equal to 110.396 with 0.000 significance level. This means that the higher the Certification the higher the performance level of the MTs.Negeri Model Teacher of West Lombok, the lower the Certification the lower the Performance of Teachers In MTs.Negeri Model Kuripan Lombok Barat. Educator's Certification, and Work Motivation have a partially significant influence on Teacher Performance in MTs in the Model Model of Kuripan West Lombok. Judging from the value of R2 Adjusted R Square, 86.6% Teacher Performance is affected by Educator Certification, and Work Motivation, while the rest of 13.4% is influenced by other factors not included in this research. Of the two (2) independent variables of educator certification, and work motivation that has dominant influence on teacher performance is work motivation, because it obtains standardized value of Coefficients Beta which is bigger than other variables that is equal to 0.942.